Autoimmune disorders of neuronal potassium channels. - Newsom-Davis, J; Buckley, C; Clover, L; Hart, I; Maddison, P; Tüzüm, E; Vincent, A (2003)
Antibodies to voltage-gated potassium channels (VGKCs) appear likely to be the effector mechanisms in many patients with acquired peripheral nerve hyperexcitability (APNH) syndromes, a group of disorders that include neuromyotonia, cramp-fasciculation syndrome, and Isaacs' syndrome. They may contribute to the associated autonomic changes. Through a central action, they may also be the effector mechanism in those with Morvan's syndrome and in some patients with limbic encephalitis. Evidence supporting this hypothesis includes the increased association of APNH with autoimmune diseases (in particular, myasthenia gravis and thymoma), the response to plasmapheresis, passive transfer of APNH to experimental animals by patients' plasma or immunoglobulins, the action of their serum on VGKC currents studied in vitro, and the presence in many patients of IgG antibodies to VGKCs.